ANALISIS VALIDITAS MEDIA VIDEO PEMBELAJARAN ANIMASI BERMUATAN TRI HITA KARANA MATERI BAGAIMANA KITA HIDUP DAN BERTUMBUH MATA PELAJARAN IPAS DI SEKOLAH DASAR - I Gede Agus Arya Sudarmika; Kadek Hengki Primayana; L. Heny Nirmayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the condition where the lecture method still dominates as the main approach most commonly applied, as well as the limitations of audio-visual-based learning media that are contextually based on local content in elementary school IPAS learning. The material "How We Live and Grow" has abstract and dynamic characteristics, requiring media that can visualize concepts concretely and meaningfully for fifth-grade students. This research aims to determine the validity level of animated learning video media infused with Tri Hita Karana values on this material based on expert assessment. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Product validation was conducted by four experts, including two content experts and two media experts, using an instrument adapted from the Learning Object Review Instrument (LORI). The validation results showed an average content validity percentage of 93% with a "suitable" criterion, and an average media validity percentage of 85% with a "sufficiently suitable" criterion. The novelty of this research lies in the integration of the three dimensions of the Tri Hita Karana philosophy, namely Parahyangan, Pawongan, and Palemahan, as core content in the animated video learning media for IPAS in elementary schools, which has not been thoroughly studied in previous research. The implications of the research indicate that this media has the potential to enhance contextual learning, visualize abstract concepts interactively, and strengthen students' character and local cultural identity in line with the spirit of the Merdeka Curriculum.